Correlation between fetal mild ventriculomegaly and biometric parameters. (17th January 2019) - Fishel-Bartal, Michal; Shai, Daniel; Shina, Avi; Achiron, Reuven; Katorza, Eldad
Abstract: Introduction: The aim of this study was to assess the correlation between fetal lateral ventricle width and biometric measurements. Material and methods: A prospective study on 335 fetuses, 101 fetuses with isolated mild ventriculomegaly and a control group of 234 fetuses with a normal US examination. All fetuses underwent a detailed brain ultrasound scan and a full biometric evaluation. To further compare biometric parameters, we matched, according to gestational week and gender, 91 fetuses from the study group to 91 fetuses from the control group. Results: The mean gestational week during the exam was significantly different between the groups (29.6 weeks in the study group versus 28.3 in the control group, p = .001). The mean maternal age, obstetrical history, mode of conception, or fetal gender did not differ between the groups. After matching according to gestational age and fetal gender, the mean gestational week between the matched groups did not differ and was 29 + 5 weeks in both groups. The study group had significantly larger head circumference ( p = .009), biparietal diameter ( p < .001), femur length ( p = .023), and estimated fetal weight ( p = .024) compared with the control group. Conclusions: Isolated mild ventriculomegaly could be related to other larger fetal biometric measurements and does not necessarily mean a pathological condition.